Reputation sells: Compensation payments in the political sphere - Corinna Ahlfeld (Georg-August-Universität Göttingen, Volkswirtschaftliches Seminar, 2010)
Bargaining between different groups, which differ in objectives, preferences and interests, is at the core of political decision-making. Yet, it is logical to presume that negotiations involving more parties will lead to inertia and a slow pace in the legislative process. According to this hypothesis, political systems involving many veto-players such as federal countries or international organisations must be prone to a low activity. Oddly enough, a closer look on the European Unions' and Germany's legislation activity level shows that these are fairly high, although in both systems exist a considerably amount of opportunities to block or delay reforms. Decision-making in this framework is mostly brought about by side-payments, which are usually not reported to the public. This poses a question. If compensation payments are able to fuel the decision process by balancing interest and help to avoid reform deadlocks why are they frequently disguised? This paper addresses this question by suggesting that politicians do avoid openly paid compensation payments out of concerns over their reputation and that decision-making is rather a strategically action than showing majorities for a certain topic.
Keywords: 330; compensation; logrolling; side-payments; political reform; political economy; Politische Reform; Politische Entscheidung; Stimmentausch; Kompensationslösung; Reputation; Theorie